Cell-type specific epigenetic and transcriptional mechanisms in substance use disorder - Wang, Bin; Wang, Jiale; Beacher, Nicholas J.; Lin, Da-Ting; Zhang, Yan (Frontiers in Cellular Neuroscience, 2025)
Substance use disorder (SUD) is a chronic and relapse-prone neuropsychiatric disease characterized by impaired brain circuitry within multiple cell types and neural circuits. Recent advancements in single-cell transcriptomics, epigenetics, and neural circuit research have unveiled molecular and cellular alterations associated with SUD. These studies have provided valuable insights into the transcriptional and epigenetic regulation of neuronal and non-neuronal cells, particularly in the context of drug exposure. Critical factors influencing the susceptibility of individuals to SUD include the regulation of gene expression during early developmental stages, neuroadaptive responses to psychoactive substances, and gene–environment interactions. Here we briefly review some of these mechanisms underlying SUD, with an emphasis on their crucial roles in in neural plasticity and maintenance of addiction and relapse in neuronal and non-neuronal cell-types. We foresee the possibility of integrating multi-omics technologies to devise targeted and personalized therapeutic strategies aimed at both the prevention and treatment of SUD. By utilizing these advanced methodologies, we can gain a deeper understanding of the fundamental biology of SUD, paving the way for more effective interventions.